Comparison of Dental Arch Parameters of Three Degree of Anterior Crowding of Class I Malocclusion - Hussain A Obaidi; Ali R Al-Khatib (University of Mosul, College of Dentistry, 2006)
Aim: To assess the relation between the anterior dental crowding in Class I molar occlusion with the dental arch parameters in both dental arches and for both sexes. Materials and Methods: This study presented data from examination of the study casts for a sample of 106 maxillary and 142 mandibular dental arches of pupils of the intermediate school in Mosul City aged 12-15 years of Iraqi origin. The sample was divided into three main groups according to anterior dental crowding degree (0-2.0 mm, 2.1-4 mm and over 4.0 mm). This was done by calculation of dental arch space available (dental arch perimeter) by utilizing the segment arch technique. The six segment technique assessed by using a modified sliding caliper gauge. The mesio-distal crown width of each tooth was measured, to get the space necessary, and the difference between the space available and the space necessary is negative value represent the amount of crowding. The data was analyzed utilizing statistical analyses at p≤0.05 significant level. Results: all the dental arch parameters were insignificantly decreased throughout the three groups accompanied by increase in the degree of anterior dental crowding except the dental arch perimeter which decreased significantly, while intercanine and the canine-molar parameters were insignificantly increased in both dental arches and for both sexes. Conclusion: The inter-canine parameter increase in crowding case whereas the other parameters are decrease.